Dimensional stability of cotton / acrylic plain knitted structure produced with flat-bed knitting / E. Nasir... [et al.] - E., Nasir; T., Dias; N., Tulos; A., Musa; A., Baharudin; W.S., Ruznan (Universiti Teknologi MARA, Negeri Sembilan, 2013)
The project focused on the dimensional stability of plain knitted structures from soft cotton/acrylic spun yarn which were produced using flat-bed knitting machine. The test samples were knitted with four different cam settings, while the machine gauge and the number of needles used were kept constant. The test samples were then delivered to different stage of relaxations; 24 hours of dry relaxation, steaming, and washing and tumble drying. It was found that the fabric shrunk in length and width direction, whilst the stitch length was more or less constant after the relaxations. Since there was no significant variation in the stitch length, hence the dimensional change of a knitted structure during relaxation was actually influenced by the distortion of the stitch rather than changes in the stitch size.